Aspartic peptidase of Phialophora verrucosa as target of HIV peptidase inhibitors: blockage of its enzymatic activity and interference with fungal growth and macrophage interaction. (1st January 2020) - Granato, Marcela Q.; Sousa, Ingrid S.; Rosa, Thabatta L. S. A.; Gonçalves, Diego S.; Seabra, Sergio H.; Alviano, Daniela S.; Pessolani, Maria C. V.; Santos, André L. S.; Kneipp, Lucimar F.
Abstract: Phialophora verrucosa causes several fungal human diseases, mainly chromoblastomycosis, which is extremely difficult to treat. Several studies have shown that human immunodeficiency virus peptidase inhibitors (HIV-PIs) are attractive candidates for antifungal therapies. This work focused on studying the action of HIV-PIs on peptidase activity secreted by P. verrucosa and their effects on fungal proliferation and macrophage interaction. We detected a peptidase activity from P. verrucosa able to cleave albumin, sensitive to pepstatin A and HIV-PIs, especially lopinavir, ritonavir and amprenavir, showing for the first time that this fungus secretes aspartic-type peptidase. Furthermore, lopinavir, ritonavir and nelfinavir reduced the fungal growth, causing remarkable ultrastructural alterations. Lopinavir and ritonavir also affected the conidia-macrophage adhesion and macrophage killing. Interestingly, P. verrucosa had its growth inhibited by ritonavir combined with either itraconazole or ketoconazole. Collectively, our results support the antifungal action of HIV-PIs and their relevance as a possible alternative therapy for fungal infections.